Acute lower motor neuron syndrome and spinal cord gray matter hyperintensities in HIV infection. Issue 4 (August 2015) - Bogoch, Isaac I.; Wilson, Michael R.; Chad, David A.; Venna, Nagagopal
Abstract : Objective: To describe a novel manifestation of lower motor neuron disease in patients with well-controlled HIV infection. Methods: A retrospective study was performed to identify HIV-positive individuals with acute, painful lower motor neuron diseases. Results: Six patients were identified with HIV and lower motor neuron disease. Two patients met the inclusion criteria of well-controlled, chronic HIV infection and an acute, painful, unilateral lower motor neuron paralytic syndrome affecting the distal portion of the upper limb. These patients had segmental T2-hyperintense lesions in the central gray matter of the cervical spinal cord on MRI. One patient stabilized and the second patient improved with immunomodulatory therapy. Conclusions: This newly described syndrome expands the clinical spectrum of lower motor neuron diseases in HIV.